The Role of Rotational Thromboelastometry in Early Detection of the Hemostatic Derangements in Neonates with Systemic Candida Infection - Rozeta Sokou; Alexia Eleftheria Palioura; Aikaterini Konstantinidi; Alexandra Lianou; Maria Lampridou; Martha Theodoraki; Daniele Piovani; Stefanos Bonovas; Konstantina A. Tsante; Petros Ioannou; Nicoletta Iacovidou; Andreas G. Tsantes (Journal of Fungi)
Background: Systemic Candida infection (SCI) is the third most common cause of late-onset sepsis in Neonatal Intensive Care Units (NICU). While platelet involvement in fungal infections has been extensively studied, evaluation of the hemostatic mechanism in Candida infections, especially in neonates, has not been widely investigated. The aim of the current study was to evaluate the hemostatic profile of neonates with SCI through rotational thromboelastometry (ROTEM), a laboratory method that assesses the viscoelastic properties of blood. Methods: This is a single-centered prospective cohort study including a group of neonates with SCI (n = 21); the control group consisted of healthy neonates (n = 24). Demographics, clinical parameters, and laboratory data were recorded at the disease onset. Neonatal scores for the assessment of disease severity (Modified NEOMOD, nSOFA, and NeoBAT) were also calculated. ROTEM parameters of neonates with SCI were compared to those of healthy neonates. Results: ROTEM parameters differed between neonates with SCI and healthy neonates, indicating a hypocoagulable profile of infected neonates. Specifically, neonates with SCI had significantly prolonged clotting time (CT) and clot formation time (CFT), as well as lower clot amplitude at 10 min (A10) and maximum clot firmness (MCF) when compared to healthy neonates (p values < 0.05), findings that remained consistent after adjusting for confounding factors such as gestational age, birth weight, and sex. In addition, a strong correlation was noted between ROTEM parameters and disease severity based on the modified NEOMOD, nSOFA, and NeoBAT scores. Conclusions: ROTEM parameters revealed a hypocoagulable profile in neonates during the early stages of SCI, which is also associated with disease severity. The results of this study highlight the need for monitoring of hemostatic status of this vulnerable group of patients and indicate that ROTEM analysis may have a role in the early detection of the hemostatic derangements associated with SCI in neonates, in order to ensure timely diagnosis and targeted therapeutic intervention.